2021
DOI: 10.1002/bmc.5275
|View full text |Cite
|
Sign up to set email alerts
|

A novel UPLC–MS/MS method for simultaneous quantification of trigonelline, 4‐hydroxyisoleucine, and diosgenin from Trigonella foenum‐graecum extract: Application to pharmacokinetic study in healthy and type 2 diabetic rats

Abstract: Trigonelline (TR), 4‐hydroxyisoleucine (4‐HI), and diosgenin (DG) are the main bioactives of the purified standardized extract of the popular plant Trigonella foenum‐graecum L. (TFG), and it has been proven effective for the treatment of various diseases. However, to the best of our knowledge, no study has investigated the pharmacokinetic parameters of purified standardized T. foenum‐graecum extract in normal and diabetic Wistar rats. The present study has developed and validated a rapid, reliable, and sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Surprisingly, no anthocyanins could be revealed in the BC-GTE, though others have already reported their presence in BC fruits. The trigonelline and 4-hydroxy isoleucine were detected in the BC-GTE, while their incidence in the fenugreek (Trigonella foenum-graecum) was invoked to explain the associated antidiabetic properties [15]. Based on this similarity, it seems logical to predict an antidiabetic property for the BC-GTE, whereas this has already been confirmed for the fruits of BC [9].…”
Section: The Bc-gte Contains Important Flavonoids and Features Releva...mentioning
confidence: 92%
“…Surprisingly, no anthocyanins could be revealed in the BC-GTE, though others have already reported their presence in BC fruits. The trigonelline and 4-hydroxy isoleucine were detected in the BC-GTE, while their incidence in the fenugreek (Trigonella foenum-graecum) was invoked to explain the associated antidiabetic properties [15]. Based on this similarity, it seems logical to predict an antidiabetic property for the BC-GTE, whereas this has already been confirmed for the fruits of BC [9].…”
Section: The Bc-gte Contains Important Flavonoids and Features Releva...mentioning
confidence: 92%
“…In addition, extractions derived from fenugreek have been used for the treatment of diabetes, with good results. The therapeutic effects of fenugreek manifest mainly as improvements to insulin sensitivity and resistance as well as reduced fasting blood glucose and HbA1c levels 33 . These pharmacodynamic activities may be related to the flavonoids, alkaloids, volatile oils and unsaturated fatty acids derived from fenugreek 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of fenugreek manifest mainly as improvements to insulin sensitivity and resistance as well as reduced fasting blood glucose and HbA1c levels. 33 These pharmacodynamic activities may be related to the flavonoids, alkaloids, volatile oils and unsaturated fatty acids derived from fenugreek. 14 However, which compositions are most effective, the potential target genes and the mechanisms of action are not fully understood, which limits the application of fenugreek.…”
Section: Discussionmentioning
confidence: 99%
“…A few individual bioanalytical methods for the quantification of 4-HIL (Wadhwa et al, 2020), TG (Wadhwa et al, 2021), and PT (Qiu et al, 2021), excluding RFO, have been reported earlier in literature, but they were time consuming and expensive. A few molecules isolated from TFG, including isoxanthochymol, xanthochymol, garcinol, camboginol, and diosgenin, have been analyzed using LC-MS/MS techniques (Faeste et al, 2010;Wadhwa et al, 2022). The current bioanalytical method has been developed and validated for its selectivity, sensitivity, and rapid and simultaneous measurement of 4-HIL, TG, RFO, and PT in rat plasma.…”
Section: Introductionmentioning
confidence: 99%